Topological analysis of a bacterial DedA protein associated with alkaline tolerance and antimicrobial resistance. Issue 12 (16th December 2021) - Scarsbrook, Hollie L.; Urban, Roman; Streather, Bree R.; Moores, Alexandra; Mulligan, Christopher
Abstract : Maintaining membrane integrity is of paramount importance to the survival of bacteria as the membrane is the site of multiple crucial cellular processes including energy generation, nutrient uptake and antimicrobial efflux. The DedA family of integral membrane proteins are widespread in bacteria and are associated with maintaining the integrity of the membrane. In addition, DedA proteins have been linked to resistance to multiple classes of antimicrobials in various microorganisms. Therefore, the DedA family are attractive targets for the development of new antibiotics. Despite DedA family members playing a key physiological role in many bacteria, their structure, function and physiological role remain unclear. To help illuminate the structure of the bacterial DedA proteins, we performed substituted cysteine accessibility method (SCAM) analysis on the most comprehensively characterized bacterial DedA protein, YqjA from Escherichia coli . By probing the accessibility of 15 cysteine residues across the length of YqjA using thiol reactive reagents, we mapped the topology of the protein. Using these data, we experimentally validated a structural model of YqjA generated using evolutionary covariance, which consists of an α-helical bundle with two re-entrant hairpin loops reminiscent of several secondary active transporters. In addition, our cysteine accessibility data suggest that YqjA forms an oligomer wherein the protomers are arranged in a parallel fashion. This experimentally verified model of YqjA lays the foundation for future work in understanding the function and mechanism of this interesting and important family.